Provisión de las cuentas por cobrar y su efecto en los estados financieros de la compañía intvescom s.a. - Encalada Cabrera, Lucía Elizabeth (2016)
The present research project aims to help the company to carry out efficiently the provision of its accounts receivable, so if this provision does not it is correctly or simply makes it may lead the company to incur costs, such as the possible losses account, generating non-deductible expenses by bad or uncollectible accounts and this in turn leads to reduced profitability and liquidity of the company, what not you would allow make facing their obligations to short term, i.e., payment to suppliers, salaries and wages, between others. It is very important for the companies to analyze all aspects at the time of the granting of loans, establish policies that help reduce the risk of non-collection of accounts receivable, to analyze the age of portfolio and the uncollectibility of it over time…..